Estimation of the determinants for HIV late presentation using the traditional definition and molecular clock‐inferred dates: Evidence that older age, heterosexual risk group and more recent diagnosis are prognostic factors. Issue 11 (18th October 2022) - Kostaki, Evangelia Georgia; Limnaios, Stefanos; Adamis, Georgios; Xylomenos, Georgios; Chini, Maria; Mangafas, Nikos; Lazanas, Marios; Patrinos, Stavros; Metallidis, Simeon; Tsachouridou, Olga; Papastamopoulos, Vasileios; Chatzidimitriou, Dimitrios; et al.
Abstract: Objectives: HIV late presentation (LP) has been increasing in recent years in Europe. Our aim was to investigate the characteristics of LP in Greece using in addition to the traditional definition for LP, the time interval between HIV infection and diagnosis. Methods: Our nationwide sample included HIV‐1 sequences generated from 6166 people living with HIV (PLWH) in Greece during the period 1999–2015. Our analysis was based on the molecularly inferred HIV‐1 infection dates for PLWH infected within local molecular transmission clusters of subtypes A1 and B. Results: Analysis of the determinants of LP was conducted using either CD4 counts or AIDS‐defining condition at diagnosis or the time from infection to diagnosis. Older age, heterosexual transmission risk group and more recent diagnosis were associated with increased risk for LP. In contrast to previous studies, people who inject drugs (PWID) had a shorter median time to diagnosis (0.63 years) compared to men who have sex with men (MSM) (1.72 years) and heterosexuals (2.43 years). Using HIV infection dates that provide an unbiased marker for LP compared to CD4 counts at diagnosis, which are age‐dependent, we estimated that the time to diagnosis increased gradually with age. Migrants infected regionally do not differ with respect to LP status compared to native Greeks. Conclusions: We demonstrate that older people and heterosexuals are among those at higher risk for LP; and given the growing number of older people among newly diagnosed cases, tailored interventions are needed in these populations.